Brain aquaporin-4 expression in the rat septic model (immunohistochemical study) - T.V. Shulyatnikova; V.O. Tumanskiy (Medičnì Perspektivi)
The study aimed to determine aquaporin-4 expression in different brain regions was performed in Wistar rats subjected to cecal ligation and puncture (CLP) septic model. The immunohistochemical study of aquaporin-4 was carried out in the sensorimotor cortex, white matter, hippocampus, thalamus and caudate nucleus/putamen regions between 20 and 38 h after CLP. From the 12th h after CLP all animals showed the progressive impairment of sepsis signs and therefore, 9 rats were euthanized between 20-38 h (“CLP-B”, non-survived); 11 animals survived up to 48 h (constituted “CLP-A”, survived). After operation, CLP-B group displayed regionally-specific dynamic increase in aquaporin-4 level in the brain mostly associated with astroglial capillary endfeet: by 23rd h in the cortex – 234.15%, by 24th h in the thalamus –129.47% and hippocampus – 101.36%, by 30th h in the white matter – 135.31% and by 38 h in the caudate/putamen – 92.85%; with the highest increase in cortex: by 3.34 times. Heterogeneous and heterochronous aquaporin-4 elevation among brain regions indicates territories more and less susceptible for systemic toxic exposure in sepsis as well as points to diverse reactive responsiveness of local astroglial populations during specific time-period after CLP. The higher rates of aquaporin-4 in the cortex of non-survived animals in CLP model reflects the importance of aquaporin-4 increase in the mechanisms of sepsis decompensation.